Formulation for foliar and soil application of entomopathogenic nematodes for controlling the onion thrips Thrips tabaci Lindeman (Thysanoptera: Thripidae) - Hala M. S. Metwally; Mahmoud M. E. Saleh; Mokhtar Abonaem (Egyptian Journal of Biological Pest Control)
Abstract Background Onion thrips (Thrips tabaci Lindeman) are a main threat to onion (Allium cepa L.) production worldwide. Entomopathogenic nematodes (EPNs) are recommended as environmentally acceptable alternatives to chemical management for a wide range of economic insect pests. EPNs are widely used and provide good control over insect pests that live in the soil. Adjuvant-based formulation of EPN solutions has enhanced longevity and potency on foliage. In this study, tests were performed to compare two EPN application techniques for controlling the onion thrips in the open field. The first technique was the traditional spray technique, while the second one was the nematode-infected insect technique. Side experiments were conducted to investigate the influence of different adjuvants on the persistence of Steinernema feltiae (Filipjev) sprayed on onion plants in a semi-field setting. Results In semi-field experiments, the results suggested that Tween 80 or Xanthan was suitable for increasing the persistence of S. feltiae on onion plants. In the spray technique, application of Heterorhabditis bacteriophora (Poinar), at 1000 infective juveniles (IJs)/ml, combined with 0.3% Tween 80, reduced the thrips population on onion leaves by 63% in three days. However, it remained effective for only three days post-application. Using the nematode-infected insect approach, a single application of 10 H. bacteriophora-infected Tenebrio molitor L. larvae per 1 m of the row (70 cm between rows) remained effective in the onion field for 5 weeks, following treatment, generating a pest population reduction of up to 77%, while the same rates of S. feltiae reduced the pest population by up to 59%. Conclusions In onion fields, the nematode-infected insect technique was proved to be more effective and long-persisted than the traditional spray technique for controlling T. tabaci in onion fields. Further research work is still needed to improve the ease of use of the recommended approach.